Thinking-Based Learning Strategy of Ulumul Hadith for Students of Arabic Language Department of State Islamic Institute (ar) - Ade Destri Deviana; Syarifaturrahmatullah Syarifaturrahmatullah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2019)
Ulumul hadith is a science that discusses the Prophet Muhammad